Healthcare Workers and Infectious Disease Outbreaks: A Review. - Antunes, José (Clinical Medicine And Health Research Journal, 2024)
In last two decades the world assisted to an increase in the frequency of infectious disease outbreaks which are a challenge for health services and healthcare workers (HCWs). Infectious disease outbreaks cause an unexpected increase in morbidity and mortality, which in turn cause an increased demand on healthcare facilities and consequently an increase in Healthcare workers workload. A search was performed in PubMed selecting meta-analysis, reviews and systematic reviews published before July 2023. The search carried out resulted in abundant information on various aspects of HealthCare Workers’s mental health during and after infectious disease outbreaks. A substantial number of HealthCare Workers suffer greatly from a variety of psychological and psychosomatic problems. The enormous psychological burden of working under such stressful circumstances can severely affect their wellbeing and, consequently, work performance. Health policies and interventions specifically aimed at these professionals should be taken in future infectious disease outbreaks.